2018
DOI: 10.1007/s00787-018-1173-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal prenatal and postnatal anxiety on children’s emotional problems: a systematic review

Abstract: Maternal mental health problems during pregnancy and the postnatal period are a major public health issue. Despite evidence that symptoms of both depression and anxiety are common during pregnancy and the postpartum, the impact of maternal anxiety on the child has received relatively less attention than the impact of maternal depression. Furthermore, the evidence base for the direct impact of maternal anxiety during pregnancy and the postpartum on children's emotional outcomes lacks cohesion. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
102
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 48 publications
11
102
0
5
Order By: Relevance
“…Increasing child care experience could be a promising way to prevent or mitigate PPD in primiparas 39 . Perinatal maternal anxiety exposure may lead to negative outcomes in child development, and more evidence is needed 40 . When comparing primiparas and multiparas, the NP and SR subscale scores of the J-SSQ were higher in primiparas than in multiparas.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing child care experience could be a promising way to prevent or mitigate PPD in primiparas 39 . Perinatal maternal anxiety exposure may lead to negative outcomes in child development, and more evidence is needed 40 . When comparing primiparas and multiparas, the NP and SR subscale scores of the J-SSQ were higher in primiparas than in multiparas.…”
Section: Discussionmentioning
confidence: 99%
“…However, in several studies, these associations are attenuated or no longer evident after adjustment for confounders. Moreover, in the studies that included multiple informants, these associations were found using maternal but not teacher‐reported child outcomes 66 , suggesting recall bias. Interestingly, women with anxiety disorders in one study perceived themselves to have bonding problems, yet the quality of their observed mother‐infant interactions at three months postpartum was similar to the general population 67 .…”
Section: Association Between Perinatal Mental Disorders and Maternalmentioning
confidence: 97%
“…Perinatal mental health problems are a major public health issue and are associated with detrimental and enduring consequences on maternal and child health. [1][2][3][4] Depression and anxiety are the most common mental health problems during pregnancy, although prevalence rates vary by population characteristics, timing, and type of screening used. Previous systematic reviews have suggested that up to 18% of pregnant women experience depression, 14% to 54% experience anxiety, and many experience both.…”
Section: Introductionmentioning
confidence: 99%